Lincoln and emancipation - Medford, Edna Greene (Concise Lincoln library., 2015)
"In this succinct study, Edna Greene Medford examines the ideas and events that shaped President Lincoln's responses to slavery, following the arc of his ideological development from the beginning of the Civil War, when he aimed to pursue a course of noninterference, to his championing of slavery's destruction before the conflict ended. Throughout, Medford juxtaposes the president's motivations for advocating freedom with the aspirations of African Americans themselves, restoring African Americans to the center of the story about the struggle for their own liberation. Lincoln and African Americans, Medford argues, approached emancipation differently, with the president moving slowly and cautiously in order to save the Union while the enslaved and their supporters pressed more urgently for an end to slavery. Despite the differences, an undeclared partnership existed between the president and slaves that led to both preservation of the Union and freedom for those in bondage. Medford chronicles Lincoln's transition from advocating gradual abolition to campaigning for immediate emancipation for the majority of the enslaved, a change effected by the military and by the efforts of African Americans. The author argues that many players--including the abolitionists and Radical Republicans, War Democrats, and Black men and women--participated in the drama through agitation, military support of the Union, and destruction of the institution from within. Medford also addresses differences in the interpretation of freedom: Lincoln and most Americans defined it as the destruction of slavery, but African Americans understood the term to involve equality and full inclusion into American society. An epilogue considers Lincoln's death, African American efforts to honor him, and the president's legacy at home and abroad. Both enslaved and free Black people, Medford demonstrates, were fervent participants in the emancipation effort, showing an eagerness to get on with the business of freedom long before the president or the North did. By including African American voices in the emancipation narrative, this insightful volume offers a fresh and welcome perspective on Lincoln's America"--